AB0378 Improvements in Measures of Work Productivity/interference and General Health Status with Sirukumab Treatment in Patients with Active Rheumatoid Arthritis despite Disease-Modifying Anti-Rheumatic Drug Treatment. (15th July 2016) - Takeuchi, T.; Karpouzas, G.; Thorne, C.; McQuarrie, K.; Sheng, S.; Xu, W.; Peterson, S.; Ganguly, R.; Han, C.; Fei, K.; Hsu, B.
Abstract : Background: Treatment-related improvements in the ability to perform work and general health status are key outcomes from the perspective of a patient with rheumatoid arthritis (RA). Sirukumab is a human monoclonal antibody that selectively binds to the IL-6 cytokine with high affinity and is under development for RA and other diseases. Objectives: To evaluate the effects of sirukumab on work productivity/interference and general health status in patients with active RA refractory to conventional, synthetic disease-modifying anti-rheumatic drugs (DMARDs). Methods: In a randomized, double-blind, Phase 3 global study, patients with active RA and inadequate response to DMARDs were randomly assigned (1:1:1) to treatment with sirukumab SC 50 mg q4w, sirukumab SC 100 mg q2w, or placebo SC q2w. Patients on placebo with insufficient (<20%) improvement at Weeks 18 or 40 or who remained on placebo at Week 52 were re-randomized to receive treatment in 1 of the 2 sirukumab groups. The Work Limitations Questionnaire (WLQ) was used to evaluate health-related job limitations and productivity loss. The 3-level EuroQol-5 Dimension (EQ-5D) questionnaire was used to measure 5 dimensions of health status (mobility, self-care, usual activities, pain or discomfort, and anxiety or depression). The changes from baseline in the WLQ scores, EQ-5D index score (based on UK TTO), and EQ-5D health state visual analog scale (VAS) scores at Weeks 24 and 52 were evaluated as secondary endpoints. Results: Mean WLQ production loss scores improved significantly from baseline for both sirukumab 50 mg q4w and 100 mg q2w compared with placebo at Weeks 24 and 52 (all P <0.001). In addition, significantly greater improvements from baseline were also observed in all 4 mean WLQ domain scores (mental-interpersonal, output, physical demands, time management) for both doses of sirukumab compared with placebo at Weeks 24 and 52 (all P <0.05). Both the mean EQ-5D index and health state VAS improved significantly from baseline with both sirukumab doses compared with placebo at Weeks 24 and 52 (all P ≤0.002). Conclusions: In patients with active RA refractory to DMARDs, sirukumab treatment was associated with significant improvements in work-related productivity and general health status, consistent with disease improvement demonstrated with sirukumab treatment. Disclosure of Interest: T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co. Ltd, G. Karpouzas: None declared, C. Thorne Grant/research support from: Abbvie, Amgen, Celgene, Lilly, Novartis, Pfizer, Sanofi, and UCB, Consultant for: Abbvie, Amgen, Celgene, Centocor, Genzyme, Hospira, Janssen, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi, and UCB, Speakers bureau: Medexus/Medac, K. McQuarrie Employee of: Janssen Research & Development, LLC, S. Sheng Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, W. Xu Employee of: Janssen Research & Development, LLC, S. Peterson Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, R. Ganguly Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Han Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, K. Fei Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, B. Hsu Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC